PELAKSANAAN LAYANAN INFORMASI UNTUK MENGURANGI KEBIASAAN SISWA YANG MEROKOK DI SMK NEGERI 1 PADANGSIDIMPUAN - - Sukatno (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
This thesis entitled "Implementation Information Services To Reduce Smoking Habits of Students at SMK Negeri 1 Padangsidimpuan" preparation of this paper is motivated importance of knowledge about the dangers of smoking in adolescence and how to reduce the smoking habits of students in SMK Negeri 1 Padangsidimpuan.Peneitian aims to determine clearly whether there is provision Implementation Information Services To Reduce Smoking Habits of Students at SMK Negeri 1 Padangsidimpuan academic year 2014/2015. The author takes the object of research in the whole class X SMK 1 Padangsidimpuan totaling 513 people. Given the large population, the authors define the majority of the population being sampled study of 60 people that is based on grade level (stratified sampling), then the determination samples of each class carried out by random sampling. The research instrument used was a questionnaire.The method used was Quasi Experimental Desaign with nonequivalent control group design shape desaign. Data collection techniques using a Likert scale questionnaire. Data analysis techniques using the program Excel and SPSS version 20 using the Wilcoxon signed rank test and one sample kolmogrov Smirnov test. The research results can be researchers in the experimental class and control class 75.4 77.4. Test the hypothesis produce the experimental class Z on pretest-posttest with a value of -3.194 and signed pretest-posttest worth 0.01. While in the control group Z on the pretest-posttest with a value of -3.138 and signed pretest-posttest worth 0.02. At posttest posttest control experiment and signed (2-tailed) experimental class 538 and class 566 controls.In conclusion there was an increase in signefikan between pretest and posttest experiment as well as the pretest and posttest control. But the results of experimental studies hump higher than the control class. Suggestions for school research is to continue to support the provision of information services to all students.